2012
DOI: 10.1007/s00122-012-1806-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytogenetic mapping between the lima bean (Phaseolus lunatus L.) and the common bean (P. vulgaris L.)

Abstract: The common bean (Phaseolus vulgaris) and lima bean (P. lunatus) are among the most important legumes in terms of direct human consumption. The present work establishes a comparative cytogenetic map of P. lunatus, using previously mapped markers from P. vulgaris, in association with analyses of heterochromatin distribution using the fluorochromes chromomycin A3 (CMA) and 4',6-diamidino-2-phenylindole (DAPI) and localization of the 5S and 45S ribosomal DNA (rDNA) probes. Seven BACs selected from different common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 46 publications
4
46
0
3
Order By: Relevance
“…Lima bean represents an emerging model plant commonly used in studies on indirect and direct plant defense against herbivores (BallhoRn et al, 2008;, and also bacterial (yi et al, 2009) and fungal pathogens (BallhoRn et al, 2010). Furthermore, this plant is one of the most economically important Phaseolus species cultivated for food (fofana et al, 1999;alVeS et al, 2008;BonifáCio et al, 2012). To better understand the concerted effects of mycorrhizal colonization and light availability, we exposed mycorrhizal and mycorrhiza-free lima bean plants to two levels of light.…”
Section: Introductionmentioning
confidence: 99%
“…Lima bean represents an emerging model plant commonly used in studies on indirect and direct plant defense against herbivores (BallhoRn et al, 2008;, and also bacterial (yi et al, 2009) and fungal pathogens (BallhoRn et al, 2010). Furthermore, this plant is one of the most economically important Phaseolus species cultivated for food (fofana et al, 1999;alVeS et al, 2008;BonifáCio et al, 2012). To better understand the concerted effects of mycorrhizal colonization and light availability, we exposed mycorrhizal and mycorrhiza-free lima bean plants to two levels of light.…”
Section: Introductionmentioning
confidence: 99%
“…Phaseolus vulgaris (the common bean) is the most important crop species of the genus and has an enormous importance as a food resource for many human populations, especially in Africa and South America. In addition to its economic and nutritional importance, the common bean has been the focus of a number of chromosome evolution studies, making the genus an important model for plants with small genomes and high karyotypic stability [Altrock et al, 2011;Bonifácio et al, 2012;Almeida and Pedrosa-Harand, 2013;Fonsêca and Pedrosa-Harand, 2013]. This species was also used as a model for studying plant-pathogen interactions, especially in the evolution of resistance to anthracnose caused by the fungus Colletotrichum lindemuthianum [Geffroy et al, 1999[Geffroy et al, , 2000[Geffroy et al, , 2008David et al, 2008David et al, , 2009.…”
mentioning
confidence: 99%
“…Previous studies involving comparative cytogenetic mapping of khipu-containing BACs from P. vulgaris suggested either absence/very low amount of this repeat or divergence at sequence level in other Phaseolus species (Fonsêca et al 2010;Bonifácio et al 2012;Fonsêca and Pedrosa-Harand 2013;Fig. 5 Genomic organization of jumper in P. vulgaris and P. microcarpus.…”
Section: Discussionmentioning
confidence: 98%
“…Southern hybridization using a khipu probe from P. vulgaris on a range of legume genomic DNA has shown its specificity to the Phaseolus genus and revealed a large intrageneric variation in copy number ), which could also be due to significant changes at the sequence level among species. The chromosomal distribution of khipu in other Phaseolus species was not investigated, but cytogenetic mapping of khipu-containing BAC clones from P. vulgaris in P. lunatus and P. microcarpus, however, did not reveal any subtelomeric repetitive sequences in those species (Bonifácio et al 2012;Fonsêca and Pedrosa-Harand 2013) and a single hybridization site was observed in P. leptostachyus (Fonsêca et al 2015).…”
Section: Introductionmentioning
confidence: 86%